TPS Nanocomposite reinforced with MFC by melting process - Ferreira,Adriane Medeiros (2014)
Bionanocomposites of thermoplastic starch (TPS) reinforced with microfibrilated cellulose (MFC) were prepared by melt processing. MFC was prepared from eucalyptus wood pulp by a process combining cryogenic milling in high shear mixers, chemical treatment with sodium hydroxide and ultrasound treatment. The never dried MFC was then dispersed in native starch and glycerol and processed in a single screw extruder. Two MFC contents were incorporated, 3 and 10 wt %, based on TPS. The MFC was characterized by atomic force microscopy (AFM) and scanning electron microscopy (SEM). The bionanocomposites were characterized by tensile tests, SEM and water absorption experiments. Modulus and tensile strength were improved. Water absorption did not change in an appreciable way with the addition of MFC. The homogeneous dispersion of the MFC into TPS matrix can be considered one of the remarkable points of the new process used in the composite preparation.